Effect of carotid artery stenosis on collateral flow status in patients with acute ischemic stroke after mechanical thrombectomy - Jing-Liang Su; De-You Xue; Xiang-Yang Wei; Xin-Yu Yang (BMC Research Notes)
Abstract Objective Collateral circulation is critical for mitigating ischemic damage in acute ischemic stroke (AIS). This dual-center retrospective cohort study enrolled 240 patients with AIS undergoing mechanical thrombectomy (MT) aimed to evaluate how carotid artery stenosis severity affects collateral flow dynamics, functional outcomes, and 90-day survival. Results Patients divided into mild stenosis group (n = 69), moderate stenosis group (n = 117) and severe stenosis and occlusion group (n = 54). Following MT, the ASITN/SIR and BATMAN scores showed a significant increase across all groups compared to pre-MT levels (P < 0.05). However, a notable pattern emerged where both the pre-MT and post-MT scores in the severe stenosis and occlusion group were inferior to those observed in the moderate stenosis group and mild stenosis group (P < 0.05). Multivariate logistic regression showed that patients with severe stenosis and occlusion (OR = 3.09, 95% CI:2.56–3.73, p < 0.001), moderate stenosis (OR = 1.42, 95% CI: 1.13–1.78, p = 0.002), hypertension (OR = 3.36, 95% CI:1.47–7.63, p = 0.003) and T2DM (OR = 4.58, 95% CI:1.52–13.78, p = 0.006) were independent risk factors for poor collateral circulation. Kaplan-Meier curve analysis showed that the 90-day survival rate in the severe stenosis and occlusion group was lower than other groups (χ2 = 26.716, P < 0.001). These findings highlight the importance of preoperative stenosis evaluation to guide therapeutic strategies.